Men doing and undoing gender at work: A review and research agenda - Kelan, Elisabeth K. (Wiley, 2017)
While research on gender in organizations has not only documented sustained gender inequality, it has also offered an understanding of how gender is enacted through doing and undoing gender. An underexplored aspect concerns how men can do and undo gender to support or hinder gender equality processes in organizations. Doing gender is then understood as creating gender difference while undoing gender would conversely mean to reduce gender difference. The former is supporting gender inequality while the latter means moving toward gender equality. This article therefore provides a systematic review of empirical articles that discuss how men are doing and undoing gender within an organizational context. It is shown that undoing gender practices of men in organizations are under researched and a research agenda of how men can undo gender at work is thus developed. This article makes a two-fold contribution: first it offers a refinement of doing and undoing gender approaches and second, it develops a research agenda for exploring how men can undo gender at work.
Keywords: Gender; Leadership; Managers; Performativity; Practice; Work